Cavernous lymphangioma of the urinary bladder in an adult woman: an additional case report of a rare lesion and literature review - Wei He; Li Jin; Fang-fang Lin; Xiao-long Qi; Xiang-lei He; Da-hong Zhang; Ming Zhao (BMC Urology, 2021)
Abstract Background Urinary bladder lymphangioma is a rare and benign lesion that is often causes symptoms related to irritation and urinary tract obstruction. Because a lymphangioma may resemble a true neoplasm of the urinary bladder clinically, the lesion must be removed for accurate histologic diagnosis and to rule out malignancy. Case presentation We present a case of a 40-year-old female who was evaluated for painless gross hematuria. Clinical and diagnostic work up revealed a sharply defined mass involving the wall and bulging into the cavity on the dome of the bladder. Partial cystectomy was performed and histologic findings were compatible with cavernous lymphangioma. The symptom of hematuria relieved after the procedure and the patient was in good status without evidence of recurrence by cystoscopy at follow-up 6 months later. Conclusions Lymphangioma of the urinary bladder is treated with surgical excision and seems to have no recurrence once completely resected, but long-time follow-up may be needed.